A consensus‐based corporate governance paradigm for Islamic banks. (2014) - Monal Abdel‐Baki; Valerio Leone Sciabolazza
<x xml:space="preserve"> Abstract </x> Purpose – Islamic banking is a viable sustainable banking model that has shown resilience to financial crises. The aim of this research is to design a consensus‐based ethical and market‐driven corporate governance index (CGI) to boost financial performance and ensure compliance with Islamic rulings. Design/methodology/approach – The design of the CGI is the outcome of the feedback obtained from a cross‐country survey to measure bank efforts in enhancing corporate governance (CG) throughout the ten‐year period of 2001‐2011. The CGI is divided into six core CG themes and 40 sub‐themes. Findings – First, the results of the multiple regression analysis show a consistent positive relationship between CG and financial performance metrics. Second, the authors detect misaligned compensation structures for directors. Third, poor governance leads to higher risk exposures. Research limitations/implications – CG in Islamic banks is yet an evolving discipline and infant practice. This research aims to introduce a CGI that should be updated and improved as the discipline evolves. Practical implications – The research concludes by proposing a CG paradigm. The outcome of the research could also be of use to both Islamic banks and to the rapidly growing sustainable banking sector in designing a similar CGI and CG model incorporating the ethical features of sustainable finance. Social implications – The core ethos of Islam are: avoiding the exploitation of the needy, avoiding excessively risky transactions, avoiding unethical transactions and justice, equity and income redistribution. If properly applied, Islamic banking will display all features of sustainable finance as well as enhance social welfare. Originality/value – To the best of the authors' knowledge, this is the first CGI that is based on an ethical and all‐inclusive input of all stakeholders. <ack> <x xml:space="preserve"> Acknowledgements </x> JEL classification – G21, G32, P43. </ack>